Adelaide Kemble Sartoris correspondence - Kemble, Adelaide
ALS written by Sartoris to a Mrs. Tunno mentioning poets Robert Browning and Alfred, Lord Tennyson.
Opera singer and author. Sister of actress Fanny Kemble. Married John Edward Sartoris in 1843.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Browning, Robert, -- 1812-1889.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892.; Tunno, -- Mrs. -- Correspondence; Authors; Singers